Localization and Upregulation of the Nasal Histamine H1 Receptor in Perennial Allergic Rhinitis - Hideaki Shirasaki; Etsuko Kanaizumi; Nobuhiko Seki; Tetsuo Himi (Hindawi Limited, 2012)
In the present study, we have investigated the expression of histamine H1 receptor in human turbinates by RT-PCR, western blotting, and immunohistochemistry. Human turbinates were obtained by turbinectomy from 12 patients with nasal obstruction refractory to medical therapy. RT-PCR analysis of total RNA extracted from human nasal turbinate, primary cultured human nasal epithelial cells, and nasal vascular endothelial cells demonstrated the expression of histamine H1 receptor mRNA. About 56 kDa band was detected in human turbinates by western blot analysis using anti-H1 receptor antibody. The expression level of H1 receptor protein was marked in patients with nasal allergy than in patients with nonallergic rhinitis. The immunohistochemical study revealed that epithelial cells and vascular endothelial cells showed intense immunoreactivity for histamine H1 receptor. In addition, the blood vessels in superficial area expressed higher level of H1 receptor immunoreactivity than that in deeper area in the nasal mucosa. These results may have an important clinical implication for understanding the role of histamine H1 receptor on upper airway diseases such as allergic rhinitis and nonallergic rhinitis.